Evaluation of course experience with pharmacy students in Klang Valley / Nurulain Md. M. Ramli - Md. M. Ramli, Nurulain (2009)
Course Evaluation Questionnaire (CEQ) developed by Ainsley and Long (2004) is an assessment tool which consists of 25 questions that measures the undergraduate assessment of their course. The CEQ collects information of five key areas of the students experience; this being generic skills, appropriate workload, clear goal and standard and appropriate assessment. The aim of this study is to measure pharmacy students' perception of their course. From the assessment, feedback can be provided to the relevant pharmacy faculty to improve the level of higher education in the pharmacy course. Prospective study is done since data collection on the final year pharmacy students in Klang Valley was pre-planned. The questionnaires were distributed to final year pharmacy students from University Teknologi MARA (UiTM) (n=127), Universiti Kebangsaan Malaysia (UKM) (n=78) and Universiti Malaya (UM) (n=38). The relationship between CEQ ratings and institution was analysed using Kruskal-Wallis test, with the dependent variables being the five scales of CEQ. There was no significant difference in rating assigned by students in different institutions. According to the study results, improvement in scale, appropriate workload, appropriate assessment, clear goal and standard and good teaching should be conducted to further improve the quality of the course experience.